Transfer Lengths in Pretensioned Concrete Measured Using Various Sensing Technologies - Jeon, Se Jin; Shin, Ho; Kim, Sang Hyun; Park, Sung Yong; Yang, Jun Mo (International Journal of Concrete Structures and Materials, 2019)
Although pretensioned concrete structures have increasingly been used worldwide, a number of design issues need to be addressed to further improve the structural performance. Transfer length of pretensioned members was investigated with several test variables in this study by adopting various sensing technologies including the Smart Strands with embedded fiber optic sensors. The effect of increased strength in 2360 MPa high-strength strand on the transfer length was also analyzed. Representative provisions widely used in design were compared with the test results for consistency and appropriate conservatism. The strain distribution required for the transfer length depended partly on the type and location of sensors, which suggests the challenges associated with reasonable determination of the transfer length. According to the results of the analysis, the predictive equation in ACI 318 was relatively accurate and conservative under various conditions including high-strength strands. However, the transfer lengths based on the strand strains rather than the conventional surface strains of concrete require further investigation depending on the bonding behavior between the strand and the surrounding concrete inside a member. Thus, this study also introduces a new sensing technology utilizing the Smart Strand to reliably measure the strain distribution along a strand.
Keywords: Embedded fiber optic sensors; Pre-tensioned concrete; Predictive equations; Prestressing tendon; pretension; strand; Structural performance; Transfer lengths; fiber optic sensor; prestressed concrete; prestressing tendon; pretension; strand; transfer length; transmission length